Enhancing the Role of the District Government in Decentralized Forest Management - Ristianto Pribadi; Dodik Ridho Nurrochmat; Endang Suhendang; Hermanto Siregar (Jurnal Manajemen Hutan Tropika, 2020)
Following the enactment of Law Number 23 of 2014 on the Regional Government, which superseded Law Number 22 of 1999 and Law Number 32 of 2004, now the local government has no longer holds an authority to manage state forest areas, except “grand forest park” (Taman Hutan Raya) located in their respective administrative areas. The management of production forests and protected forests (located at state forest areas) is the authority and responsibility of the provincial government, while the management of conservation forests is the authority of the central government. The success of forest management and management program activities is determined, among others, by government and local government policies and their implementation at the site level. By considering ntthe complexity of forest management, the context of decentralization, and available resources as well as constrained authority, this study aims to identify the level of importance, priorities, and main roles of district governments in forest management by applying the analytic network process (ANP) method. This study suggests that the district government could play a significant role in building social capital, which serves as a first step in developing collaborative forest management by promoting the optimization of multipurpose forests to preserve forests.